2018
DOI: 10.1080/21691401.2018.1468340
|View full text |Cite
|
Sign up to set email alerts
|

Folate-molecular encapsulator-tethered biocompatible polymer grafted with magnetic nanoparticles for augmented drug delivery

Abstract: Magnetic ferrite nanoparticles (MNPs) coated with biocompatible polymers capable of drug loading and release are fascinating nanostructures for delivering anti-cancer drugs. Herein, we report the synthesis and characterization of a novel β-cyclodextrin-folate-tethered dextran polymer. Nickel-zinc ferrite nanoparticles are prepared and coated with the polymer to form a biocompatible hybrid magnetic nanocarrier. To establish the significance of folate unit of the polymer in anticancer activity, a similar derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Similarly, Blanco-Fernandez et al reported proliferation in HeLa cells after 24 h of incubation with 400 μg/mL of dextran . In addition, a wider range of concentrations was evaluated, finding the IC50 at 2282 μg/mL (Figure B) that is 100 times higher than the value reported for a β-cyclodextrin-folate-tethered dextran conjugate by Ramasamy et al, 2018 (approximately 20 μg/mL), in the same cell line, suggesting that the conjugate fabricated in this research shows high biocompatibility …”
Section: Resultssupporting
confidence: 66%
“…Similarly, Blanco-Fernandez et al reported proliferation in HeLa cells after 24 h of incubation with 400 μg/mL of dextran . In addition, a wider range of concentrations was evaluated, finding the IC50 at 2282 μg/mL (Figure B) that is 100 times higher than the value reported for a β-cyclodextrin-folate-tethered dextran conjugate by Ramasamy et al, 2018 (approximately 20 μg/mL), in the same cell line, suggesting that the conjugate fabricated in this research shows high biocompatibility …”
Section: Resultssupporting
confidence: 66%
“…Some of non-viral carriers were designed and developed to overcome the challenges of ineffective DNA-endosomal capture and release from the carrier vector into the nucleus, and represent a promising methods for gene delivery purposes [10]. Superparamagnetic iron oxide NPs (SPIONs) are widely used for biomedical applications, such as target gene delivery systems and gene therapy, It can be used also in cancer chemotherapy as drug carrier after coated with biocompatible polymers [11,12] SPIONs with unique magnetic properties are being actively investigated as magnetic resonance imaging contrast agents [12], It can be properly designed and engineered to reach their target tissue with less nonspecific cellular interactions [13,14]. In addition, SPIONs showed a high labeling efficiency in different mammalian cell types [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different organic and inorganic materials, such as polymeric nanoparticles, metallic nanoparticles, liposomes, etc., have been studied as drug delivery carriers. 176 Therapeutic agents like drugs, 178 genes, 179 growth factors, 180 and enzymes 181 an external magnetic field. 11,12 To enhance drug delivery efficiency of nanoparticles, multiple parameters ( Figure 6) should also be adjusted:…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Furthermore, different organic and inorganic materials, such as polymeric nanoparticles, metallic nanoparticles, liposomes, etc., have been studied as drug delivery carriers 176 . Therapeutic agents like drugs, 178 genes, 179 growth factors, 180 and enzymes 181 can be loaded on MNPs, especially SPIONs. MNPs are one of the most suitable carriers for delivering bioactive molecules because of their unique advantages, especially the ease with which they can be monitored and visualized through MRI with guidance from an external magnetic field.…”
Section: Various Metallic and Metallic Oxide Nanoparticles Used In Ormentioning
confidence: 99%